Exhibiting Settler Geology: The Geological Survey of Canada’s 19th Century Mineral Collections - Laura Pannekoek (Museum & Society)
This paper studies the Canadian mineralogical collection sent to the 1851 Great Exhibition in London. This mineralogical collection was curated by William Logan of the Geological Survey of Canada that played a key role in  fossil fuel exploration,  colonial expansion, and settler statecraft in Canada in the 19th century. This collection was a key moment in the development and funding of the large-scale transcontinental geological surveys that followed in the second half of the 20th century in Canada. In this paper, I argue how the 1851 exhibition initiated pathways for international investment in marking the beginning of the planetary scope of the Canadian mining industry today.